Design and Application of Full Digital Control System for LLC Multiresonant Converter - Špánik, P.; Drgoňa, P.; Frívaldský, M.; Príkopová, A. (Elektronika ir Elektrotechnika, 2010)
With use of microprocessors and digital signal controllers as a control systems in power semiconductor converters, the new approaches for design of digital control must be implemented. Designing a digital control system requires use of control to output transfer function. For new, frequency controlled resonant converters, like LLC converter, new simulation based, numerical methods must be employed. This paper deals with new method for revealing the transfer function. For proposal of optimal controller, the direct digital design was used. Verification of designed digital control system is shown at the end of paper.